Forged Marksheet detection System Using QR code - Pandey, Sanjeev kumar; Patel, Rahul; Ubale, Sanket; Lokare, DA (International Journal of Computer Sciences and Engineering, 2015)
Digital world requires digital data, so it is important to optimize the data accordingly. Therefore it is important to preserve the digital space for saving digital data. This paper presents an Alternative way to optimize the digital data by utilising the technique of QR code. This QR code is obtained by encrypting the normal digital data. Here in this paper, we are utilising this technique to design Digital Marksheet system. Here the digital data would be the students record which would be saved using QR code because this optimize technique is secure and quite useful. We would be using .NET platform to design the system. This paper provides a new dimension for storing, accessing and authenticating the digital data.